COST-EFFECTIVENESS OF APIXABAN AS COMPARED WITH WARFARIN AND ACETYLSALICYLIC ACID IN PATIENTS WITH NON-VALVULAR ATRIAL FIBRILLATION IN THE RUSSIAN FEDERATION - A. V. Rudakova; V. A. Parfenov (Рациональная фармакотерапия в кардиологии, 2015)
Background. For prevention of thromboembolic events in patients with non-valvular atrial fibrillation (NVAF) the following types of antithrombotic therapy are used: anticoagulant therapy with vitamin K antagonists (such as warfarin), antiplatelet therapy (such as acetylsalicylic acid) and novel oral anticoagulants such as apixaban, rivaroxaban and dabigatran. Administration of vitamin K antagonists (VKA) is complicated by the need for individual dose adjustment and frequent monitoring of international normalized ratio (INR). Both warfarin and acetylsalicylic acid are widely used for thrombosis prevention in patients with NVAF in the Russian Federation.Aim. To evaluate the cost-effectiveness ratio of apixaban compared with warfarin and acetylsalicylic acid in patients with NVAF from the Russian Federation national health care system perspective.Material and methods. This analysis used a Markov model that allowed estimation of the incremental cost-effectiveness ratio (ICER) for apixaban as compared with warfarin and acetylsalicylic acid over lifetime horizon in VKA suitable and VKA unsuitable patients with NVAF respectively. The model enclosed cardiovascular event rates based on the results of the randomized clinical trials comparing clinical effectiveness and safety of apixaban with warfarin (ARISTOTLE) and acetylsalicylic acid (AVERROES). The following cardiovascular events were taken into consideration: ischemic and hemorrhagic stroke, systemic embolism, intracranial hemorrhage, other major bleeds, clinically relevant non-major bleeds and myocardial infarction. Direct medical costs were determined based on the rates of the compulsory national medical insurance system. The price of the antithrombotic drugs was taken as a weighted average tender price for the year 2013. In the model both costs and benefits (quality-adjusted life years and life-years) were discounted at 3.5%. Cost-effectiveness threshold was set at 1.4 million rubles per quality-adjusted life year (QALY) gained and corresponded to the three times GDP per capita in 2013 in the Russian Federation. Sensitivity analysis explored the impact of the treatment discontinuation rates, patients’ age and quality of INR monitoring on the cost-effectiveness of apixaban.Results. In the base case analysis it was demonstrated that apixaban as compared with warfarin and acetylsalicylic acid provided additional 0.187 and 0.255 life years as well as additional 0.187 and 0.214 QALYs respectively. Over lifetime horizon apixaban as compared with warfarin and aspirin required additional treatment costs equal to 112.72 and 101.35 thousands rubles, respectively. With that estimated incremental cost-effectiveness ratio for apixaban as compared with warfarin and acetylsalicylic acid was 603.92 and 473.02 thousands rubles per QALY respectively. The results were robust in sensitivity analysis.Conclusions. Apixaban is expected to be a cost-effective alternative to warfarin and acetylsalicylic acid in patients with NVAF from the Russian Federation national health care system perspective. Apixaban may be recommended for inclusion into formulary reimbursement lists as an alternative to warfarin.